Peritonsillar Block with Triamcinolone as a Preemptive Analgesia in Tonsillectomy with Bipolar Electrocauter - Firdaus, Faundra Arieza (Journal of Anaesthesia and Pain, 2024)
Background: Tonsillectomy is one of the common types of ear, nose, and throat (ENT) surgery. Patients undergoing tonsillectomy frequently experience significant postoperative pain due to oropharyngeal muscle spasms and irritation of afferent nerve fibers. According to previous studies, triamcinolone for peritonsillar block was used to reduce postoperative pain in patients who have undergone tonsillectomy. The aims and objectives of this study were to observe the effectiveness of peritonsillar block using triamcinolone for reducing pain in patients with post-tonsillectomy using the bipolar electrocautery technique.Case: A 34-years-old male patient with chronic tonsillitis and obstructive sleep apnea (OSA) was undergoing tonsillectomy with general anesthesia and peritonsillar block after general anesthesia with triamcinolone 0,5 mg/kg body weight in the right and left fossa peritonsillar. Postoperative hemodynamic monitoring was carried out in the inpatient room. Patients were assessed for pain scale after tonsillectomy and side effects of triamcinolone, with pain indicator using the Wong-baker faces pain rating scale, numeric pain rating scale, and Face, legs, activity, cry and consolability (FLACC) Scale. Pain scales were assessed 1 hour after the tonsillectomy in the recovery room, 3 hours after the tonsillectomy in the inpatient room, 8 hours after the tonsillectomy in the inpatient room, 1 day after the tonsillectomy in the inpatient room, and 2 days after the tonsillectomy by phone. The patient went out of the hospital after 1 day of tonsillectomy.Conclusion: Peritonsillar block with triamcinolone is effective in reducing pain after tonsillectomy and can be the drug of choice when administering peritonsillar block.